Integration strategies of a leaf-cutting ant social parasite. (October 2015) - Nehring, Volker; Dani, Francesca R.; Turillazzi, Stefano; Boomsma, Jacobus J.; d'Ettorre, Patrizia
Abstract : To enter and integrate into host nests, ant social parasites employ a variety of behavioural and chemical strategies for bypassing host defences. Alternative chemical strategies are often considered separately, because only one is assumed to be effective in each particular species or in specific phases of the usurpation process. We studied the integration process of inquiline social parasite queens of Acromyrmex insinuator into nests of its host, the leaf-cutting ant Acromyrmex echinatior . When transplanted to a new host colony, parasite queens were initially attacked but later accepted by host workers, while non-nestmate host queens were always killed in this process. Parasite queens were more readily accepted by host colonies that already contained a parasite queen. The cuticular chemical profiles of parasite queens appeared to be specific to a host colony and parasite queens had higher amounts of cuticular n -alkanes than host queens, a substance class that is typically not relevant for nestmate recognition. We found evidence for two chemical strategies that are not mutually exclusive: (1) increased n -alkane levels suggest chemical insignificance, i.e. that parasites are able to enter host colonies because crucial recognition labels are absent, and (2) colony specificity of labels and attacks by non-nestmate host workers suggest that camouflage, a gradual acquisition of host colony-specific labels during integration, applies as well. We argue that combining insignificance and camouflage may be synergistically adaptive for intruding inquiline queens when this leads to a higher likelihood of achieving permanent acceptance. Highlights: Acromyrmex insinuator is an inquiline of the related leaf-cutting ant Acromyrmex echinatior . Parasite queens are attacked by non-nestmate host workers, but not by nestmates. Parasites bear a colony-specific recognition label, suggesting chemical camouflage. Parasite queens bear higher amounts of linear alkanes than host queens. Chemical camouflage and insignificance may work in synergy.